What are The Most Effective Pharmacological and Non-Pharmacological Interventions for Managing Progression of Cerebral Atrophy in Patients with Neurodegenerative Disorders? : A Systematic Review - Franky Abryanto; Anistia Wigata; Susi Susanti Gurning (International Medical Journal Corp. Ltd, 2025)
Introduction: Cerebral atrophy, a hallmark of neurodegenerative disorders like Alzheimer's (AD) and multiple sclerosis (MS), leads to cognitive and functional decline. Identifying effective pharmacological and non-pharmacological interventions to slow this progression is crucial for improving patient outcomes. Methods: This systematic review followed PRISMA 2020 guidelines, including RCTs, systematic reviews, meta-analyses, or longitudinal observational studies of adults with neurodegenerative disorders. Studies required validated neuroimaging (MRI/CT) for atrophy assessment, minimum 6-month follow-up, and quantitative brain volume measures. A PICO-based keyword strategy was used for database searches. Results: Thirty-one studies were included, predominantly focusing on MS and AD. Pharmacological interventions, especially in MS, consistently reduced brain atrophy rates. Cholinesterase inhibitors and memantine showed small but significant effects in AD. Non-pharmacological interventions like exercise and cognitive rehabilitation preserved brain structure and improved function, particularly in early-stage disease or cognitively impaired individuals. Combined interventions showed additional benefits in AD. Discussion: Pharmacological agents like siponimod and ibudilast demonstrated robust atrophy reduction in MS. In AD, cholinesterase inhibitors and choline precursors reduced gray matter atrophy. Non-pharmacological approaches, such as exercise with music, preserved medial temporal lobe integrity and daily living activities. While direct comparisons are sparse, pharmacological interventions appear more potent in MS, while combined approaches excel in AD. Early intervention and patient neural reserve significantly influence efficacy. Conclusion: Effective cerebral atrophy management demands disease-specific, early, and tailored interventions. Pharmacological interventions show strong structural benefits in MS and AD, while non-pharmacological and multimodal approaches offer complementary advantages, especially in early-stage disease. Future research should prioritize head-to-head comparisons to optimize treatment protocols and improve long-term outcomes.